Dendritic integration of sensory information in perceptual decision-making - Groschner, L (2018)
Perceptual decisions require the temporal integration of sensory evidence to a response threshold. How the brain performs this operation is unknown. In fruit flies, expression of the forkhead box P transcription factor (FoxP) in αβ core (αβc) Kenyon cells of the mushroom bodies influences decision times in odour discrimination tasks. Flies with a hypomorphic mutation in the FoxP locus take longer to commit to a choice than wild-type flies, especially in difficult tasks. Using calcium imaging and patch clamp electrophysiology in vivo, I investigate how FoxP shapes the biophysical properties of αβc neurons and link these properties to the flies’ olfactory decision-making behaviour. I find that αβc Kenyon cells integrate individual odour-evoked synaptic inputs to action potential threshold at time scales matching the speed of olfactory discrimination. FoxP, by controlling the abundance of the voltage-gated potassium channel Shal (KV4) in αβc Kenyon cell dendrites, determines the integrative properties of these neurons and dictates decision times. Targeted expression of dominant-negative or functional Shal in αβc Kenyon cells is sufficient to correct or reproduce, respectively, the FoxP mutant phenotype. Subthreshold dynamics in membrane voltage thus have a previously unrecognised influence on temporal aspects of decision-making.